1975
DOI: 10.1159/000119584
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of the Prone Position for Neurosurgical Procedures on the Upper Cervical Spine and Posterior Cranial Fossa in Children

Abstract: The authors have reviewed the charts of 107 patients undergoing 119 surgical procedures in the prone position for posterior fossa or upper cervical lesions. The intraoperative complications encountered include cardiac arrhythmia, respiratory complications, cardiac arrest, hypothermia, air embolus and technical difficulties. In all but three children the problems were minor and easily remedied. The use of controlled ventilation appears to reduce blood loss, permits excellent relaxation of the exposed tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Cardiovascular collapse during neurosurgical operations is not uncommon, especially in patients with large, vascular tumors, where blood loss can be torrential. 6,7 This is especially true in children undergoing neurosurgery, where profuse blood loss can cause life-threatening hemodynamic instability. Many of these operations are performed in the sitting, lateral, and prone positions, hindering conventional resuscitation and further compounding the dangers associated with cardiovascular instability.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular collapse during neurosurgical operations is not uncommon, especially in patients with large, vascular tumors, where blood loss can be torrential. 6,7 This is especially true in children undergoing neurosurgery, where profuse blood loss can cause life-threatening hemodynamic instability. Many of these operations are performed in the sitting, lateral, and prone positions, hindering conventional resuscitation and further compounding the dangers associated with cardiovascular instability.…”
Section: Discussionmentioning
confidence: 99%
“…For procedures in the pediatric patient it has been well shown that the prone position yields adequate exposure while substantially reducing the operative risks [5,6], The infratentorial approach in the prone position. while allowing and improving patient safety, is confounded in its exposure of the high cerebellum and parapineal region [8], A distinct disadvantage is the need to work over the superior aspect of the cerebellum and beneath the tentorium [8], Bridging cerebellar veins are encountered and must be interrupted [6,9], It is of interest that Cushing [3] described 2 cases of bleeding from this high cerebellar region via the infratentorial approach with 1 death.…”
Section: Discussionmentioning
confidence: 99%
“…The occipital transtentorial approach has been previously described by various authors for exposure of the pineal region [5,[7][8][9], With the introduction of the operating microscope the occipital approach allows relatively safe access to the previously difficult pineal region. It is our expe rience, however, that this procedure allows a good exposure of the superior part of the infratentorial compartment.…”
Section: Introductionmentioning
confidence: 99%
“…The chest is then supported on pillows or a foam pad. The full frame has been advocated by Humphries and colleagues [20] for use in neurosurgical procedures on the upper cervical spine and posterior fossa in children. Mouradian and Simmons [33] have described a method of combining the Foster or Stryker frame with the Relton and Hall frame so that continuous skeletal traction may still be applied whilst the patient is undergoing surgery.…”
Section: Influence Of Reconstructive Spinal Surgerymentioning
confidence: 99%